Synthesis and future research directions - Teerikangas, Satu (Edward Elgar Publishing, 2021)
This chapter synthesizes the findings on sustainability agency gathered across the handbook's chapters. Each of the handbook's chapters reviewed a particular type or angle to sustainability agency, within a discipline or literature, often crossing disciplines. In this synthesis chapter, based on a meta-review of the handbook's chapters, we integrate the findings from across the handbook, thus offering an integrative perspective on sustainability agency. This chapter starts with a methods-based overview of the review approaches adopted across the handbook's chapters, alongside methods-related future research directions. The second section offers a meta-review of the handbook's chapters as regards the concepts of sustainability, agency, and sustainability agency, alongside the chapters' theoretical underpinnings. This meta-review leads us to define sustainability agency and to identify its characteristics and paradoxical nature. In the third section, we discuss research gaps and offer directions for future research on sustainability agency. Section four concludes the handbook.